Pendeteksian Plagiarisme Skripsi Menggunakan Algoritma Levenshtein Distance Berbasis Web - Ckristian Hutagalung (Journal of Computer System and Informatics (JoSYC), 2019)
Plagiarism is a violation that often occurs and deserves attention. Because the act of plagiarism is the act of plagiarizing other people's work and acknowledging it as a personal work. Therefore, the detection of plagiarism needs to be done to reduce plagiarism of the work of others. This study aims to detect the similarity of the title of the thesis text using the Levenshtein Distance algorithm so that it can be used to help determine plagiarism. The stages in the system are preprocessing which consists of case folding, tokenizing, filtering, stemming, sorting. After the preprocessing process, the next step is to calculate using the Levenshtein Distance method by measuring the similarity value so that it gets a similarity percentage value between the two titles. In this thesis, the author uses the Levenshtein Distance method is a string matrix used to measure the difference or distance between two strings